Newnes electrical pocket book - Reeves, E. A. (Butterworth-Heinemann Book, 1992)
Newnes Electrical Pocket Book, Twenty-first Edition, provides engineers with convenient access to various facts, tables, and formulae relating to the particular branch of engineering being dealt with. In the case of electrical engineering, it is essential that the engineer have a clear understanding of the methods by which the various formulae are derived to ensure that any particular formulae is applicable to the conditions being considered. The first section of the Pocket Book is devoted to the theoretical groundwork upon which all the practical applications are based. This covers symbols,